Prompting Probing Learning Method: Active, Innovative, and Encouraging Students to Understand Fikih Material Quickly - Nisa Nurpadilah; Imam Tabroni; Hilwa Tsamrotul Fuadah; Wangi Budianingrum; Wilda Awaliah (International Journal of Integrative Sciences, 2023)
Activeness of students in the learning process is very important to achieve the learning process, talent in speaking in front of the class. Therefore this research is motivated by several problems that occur in MI Al – Muhajirin Plered Purwakarta in learning Islamic Religious Education, one of the problems that occurs is the low student learning activity which is motivated by monotonous learning so that students feel bored in the learning process cause students are not active in the learning process. To solve the following problems, it is assumed to use the Probing Promting method with media images, where this application is implemented in class III by paying attention to the learning curriculum that has been set in educational units such as lesson plans and syllabus. This study uses Classroom Action Research, which is conducted in 2 cycles. The research was conducted in class III with 29 students. The results obtained in this study increased the activeness of student learning. Cycle 1 results of observations of student learning activeness obtained a percentage of 73.28% categorized as active reinforced by the results of a questionnaire on student learning activeness with a percentage of 76.19% categorized as active. Cycle II, the results of observing student learning activeness obtained a percentage of 86.78%, categorized as very active, reinforced by the results of a questionnaire on student learning activeness, with a percentage 84.41%